Persepsi Petugas Customer Relation Officer Dalam Service Recovery Rekomendasi Hak Guna Bangunan di Atas Hak Pengelolaan Lahan - Putri, Ayu Adriana; Fitriati, Rachma (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
The purpose of this study is to describe what factors increase CRO's adaptability in service recovery on HGB over HPL in the Capital Investment Office and the One Stop Integrated Ministry of DKI Jakarta Province. The method used in this research is quantitative descriptive. Sources of data were taken from CRO officers who were directly involved in HGB services over HPL as many as 50 respondents. The technique of collecting data is done by distributing and filling out questionnaires. The results found that cultural competence, self-management, social capacity affect recovery Performance and information justice factors do not influence the Performance of CRO recovery services on HGB search services over HPL.